Policing in the Era of Permissiveness: Mitigating Misconduct Through Third-Party Standing - Cook, Julian A. (2016)
On April 4, 2015, Walter L. Scott was driving his vehicle when he was stopped by Officer Michael T. Slager of the North Charleston, South Carolina, police department for a broken taillight. A dash cam video from the officer’s vehicle showed the two men engaged in what appeared to be a rather routine verbal exchange. Sometime after Slager returned to his vehicle, Scott exited his car and ran away from Slager, prompting the officer to pursue him on foot. After he caught up with Scott in a grassy field near a muffler establishment, a scuffle between the men ensued, purportedly over a Taser in Slager’s possession. A bystander began filming the confrontation at this point, capturing Slager firing his Taser at Scott, the two men tussling, something falling to the ground, and Scott subsequently attempting to flee. With Scott’s back to the officer, Slager, while in an upright, stationary position, fired eight shots in Scott’s direction, striking him several times and causing him to fall face down to the ground. After approaching Scott, Slager placed him in handcuffs before calling and reporting to dispatch that Scott was “down” and that “[h]e took my Taser.” About 90 seconds later, Slager contacted dispatch for a second time. This time, he reported that Scott was unresponsive and had suffered wounds to various parts of his body. Scott, who was African-American, died at the scene. He was 50 years old. On June 8, 2015, Slager, who is white, was indicted for first-degree murder. The Walter Scott shooting is but one of a steady stream of police misconduct cases of late involving white officers and black individuals that have generated significant media coverage and public conversation. The Staten Island, New York, chokehold case involving Eric Garner, the Cleveland, Ohio, death of Tamir Rice, who was 12 years old and was carrying a fake gun in a public park when he was shot by a police officer, the shooting death of Michael Brown at the hands of a police officer after a confrontation in Ferguson, Missouri, and the Sandra Bland incident in Hempstead, Texas, where she was stopped for a traffic violation, threatened by an officer with a Taser, and later found dead in her jail cell, are among the notable events that have thrust the issue of police misconduct back into the national spotlight. Whereas the Warren Court era was characterized, in part, by its expansive protections of individual constitutional liberties, the Supreme Court in the years since has steadily—and significantly—undermined many of these outcomes. With the weakening of constitutional safeguards has come an expansion of law enforcement’s authority to perform their investigative functions and a corrosive influence on police organizational culture. This article argues that the Court’s post-Warren era of investigative permissiveness has contributed to what Professor Barbara Armacost describes as “an overly aggressive police culture” that is increasingly emboldened by highly favorable search and seizure, interrogation, and identification laws and extremely limited—and forgiving—exclusionary rule jurisprudence. The goal of this article is to build upon the academic literature relevant to the issue of policing and offer a pragmatic, remedial measure that provides incentives to police agencies to improve their institutional culture and become more constitutionally compliant. By focusing on the Supreme Court’s jurisprudence in the Fourth Amendment exclusionary rule and standing contexts, this article demonstrates how the Court, over the course of many years, has contributed to this problematic police culture and thus to the associated problems of police malfeasance. In the end, the article proposes an unprecedented expansion of the standing doctrine. It argues that as more aggrieved individuals are empowered to challenge constitutionally questionable police conduct, institutional cultures will, in turn, adapt to this new reality, thereby producing a climate that fosters greater respect for constitutional liberties, discourages unnecessarily aggressive police behaviors, and improves relations between law enforcement and the majority and minority communities they serve